溫鍼의 표준화를 위한 애주의 밀도에 따른 온도 측정 硏究 - 김윤홍; 이승호; 여수정; 최일환; 김영곤; 임사비나 (대한한의학회, 2008)
Objectives: Warm-needling is a method combining the effects of acupuncture with the effects of moxibustion. We need to standardize the characteristics of warm-needling in order to achieve consistency in its operational mechanisms and effects, which will improve clinical ability in the field of Eastern medicine. Methods: In this study, using the LabVIEW system on the warm-needling technique, we measured and compared partial temperature changes which varied according to the density of the moxa cone and the moxa cone's core peak temperature. Results& Conclusions: Examination of the warm-needle's partial temperature in relation to the cone density of the 0.8g moxa specimen suggests that a lower density of the moxa cone corresponds to a higher peak temperature and but with a shorter duration. During the effective stimulus time, the lower the density of the moxa cone, the shorter the duration of the effective stimulus time and the higher the mean temperature. Conversely, the higher the density of the moxa cone, the longer the effective stimulus time and lower the mean temperature.